алгебра 7 класс решебник

Номер 683

 

Условие:

Представьте в виде многочлена выражение:
а) (х2 + ху - у2) (х + у); б) (n2 - nр + р2)(n - р);
в) (а + х)(а2 - ах - х2);   г) (b - с) (b2 - bc - с2);
д) (а2 - 2а + 3)(а - 4);    е) (5х - 2)(х2 - х - 1);
ж) (2 - 2х + х2)(х + 5);  з) (3у - 4)(у2 - у + 1).

 

Ответ:

a) 2 + ху - у2)(x + y) = x3 + х2y + х2y + xy2 - xy2 - y3 = x3 + 2х2y - y3;
6) (n2 - nр + р2)(n - p) = = n3 - n2p - n2p + np2 + np2 - p3 = n3 - 2n2p + 2np2 - p3;
в) (a + x)(а2 - ах - х2) = a3 - a2x - aх2 + a2x - aх2 - x3 = a3 - 2aх2 - x3;
г) (b - c)(b2 - bc - с2) = b3 - b2c - bc2 - b2c + bc2 + c3 = b3 - 2b2c + c3;
д) (а2 - 2а + 3)(а - 4) = a3 - 4a2 - 2a2 + 8a + 3a - 12 = a3 - 6a2 + 11a - 12;
e) (5x - 2)(х2 - х - 1) = 5x3 - 5х2 - 5х - 2х2 + 2x + 2 = 5x3 - 7х2 - Зx + 2;
ж) (2 - 2х + х2)(x + 5) = 2x + 10 - 2х2 - 10x + x3 + 5х2 = x3 + 3х2 - 8x +10;
з) (Зу - 4)(у2 - у + 1) = 3у3 - 3у2 + 3у - 4у2 + 4у - 4 = 3у3 - 7у2 + 7у - 4.